Clinical Classification of Urethrocutaneous Fistulas Developing after Hypospadias Repair - Singh, Abhinav; Singh, Malika; Singh, Raghubir (Indian Journal of Plastic Surgery, 2023)
Background Clinical classification of the urethrocutaneous fistulas (UCFs) was designed to help the surgeons in (1) categorizing the fistulas, (2) selecting appropriate treatments, (3) keeping record at presentation and discharge, and (4) transferring information while referring a patient with recurrent fistula to a higher center.Methods This retrospective study comprised of 68 patients with UCFs who reported in the “Hypospadias and VVFs Clinic” between 2004 and 2016. The study was performed to determine the incidence or etiology of the UCFs. It was rather performed to classify fistulas into different categories depending on the number of fistulas: A (5 fistulas), B (16 fistulas), C-a (28 fistulas), C-b (4 fistulas), D (4 fistulas), and E (11 fistulas). Category A fistulas healed conservatively. Category B fistulas underwent transection of the fistula tracts (tractotomy), purse-string closure, or multilayered closure (fistulorrhaphy). Category C-a fistulas were reenforced by preputial or penile skin flaps or waterproofing flaps. Category C-b fistulas underwent re-tubularization of their neourethral plates and eccentric closure of peno-preputial skin. The urethral plates of category D fistulas were re-tubularized after 3 to 6 months and cover was provided by the Cecil-Culp procedure. Category E fistulas had associated hairy urethra, stricture distal urethra, stricture with diverticulum, perifistular scar-induced chordee, long narrow urethral plate, balanitis xerotica obliterans (BXO), and short reconstructed neourethra. Accordingly, appropriate corrective measures were taken. Miscellaneous category F was excluded from the study.Results Except for one in category D, none of the patients had any recurrence of fistula. One patient of category E had residual diverticulum.Conclusion The designed clinical classification of UCFs is simple. Treatment was in accordance with reconstructive ladder wherein complexity of treatment paralleled with increasing complexity of fistulas.
Keywords: classification; urethrocutaneous fistulas; reconstructive ladder